Effect of scrubbing medium's particle size distribution and scrubbing time on scrubbing flotation performance and entrainment of microcrystalline graphite. Issue 10 (3rd October 2022) - Wang, Xuexia; Bu, Xiangning; Alheshibri, Muidh; Bilal, Muhammad; Zhou, Shaoqi; Ni, Chao; Peng, Yaoli; Xie, Guangyuan
ABSTRACT: In this study, we investigated the effect of the scrubbing medium's particle size distribution on the scrubbing flotation performance of microcrystalline graphite. A simplex lattice mixture design approach using Design-Expert software was employed for proportioning testing of the scrubbing media. Three different sizes of scrubbing medium (A: 1 mm, B: 2 mm, and C: 3 mm) were mixed to obtain different particle size distributions. The results showed that a linear mixture model was suitable for fitting this mixture design, and the particle size distribution of the scrubbing medium was 3 mm. Hence, we studied the effect of scrubbing time on the flotation performance of the scrubbing flotation process. The flotation results indicated that graphite quality was enhanced by increasing the scrubbing time, and the optimum scrubbing time for this graphite was 45 min when maximum enrichment efficiency was acquired. Also, we investigated the effect of the scrubbing medium's particle size compositions on gangue entrainment in the scrubbing flotation process. It was concluded that the degree of entrainment under the composition of scrubbing size 1 mm (16.67%), 2 mm (16.67%), and 3 mm (66.66%) was reduced compared to the other two compositions (scrubbing size 2 mm (50%) and 3 mm (50%) as well as scrubbing size 3 mm (100%)). This conclusion was proved using analyses of froth bubble size and scanning electron microscopy and energy dispersive x-ray spectroscopy (SEM-EDS).